Developing a remote control for digital data transmission using infrared and rario frequency : wireless communication - Khandaker, Shahidur; Shailee, Shirajim Monira (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.